(untitled) (Research, Society and Development, 2021)
The present study aimed to investigative the micrbiological quality of Brazil nuts sold in open markets in the city of Macapá-AP. Samples of fresh almonds were collected at 3 open markets in Macapá from September to October 2018. Microbiological analyzes for thermotolerant coliforms and Salmonella sp were performed according to procedures described by MAPA (Ministry of Agriculture, Livestock and Supply) 62, of August 26, 2003 and the results compared with RDC nº 12, of January 2, 2001. The results showed the presence of levels of thermotolerant coliforms above the limits established by the legislation in at least one sample of each evaluated fair, being presence of Salmonella sp. The analysis results indicate that all fairs presented unsatisfactory samples, corresponding to 33,33% of the total in fairs I and III and 66,67% at fair II. Therefore, the analyzes point to the need to intensify sanitary inspection, as well as to devise more effective actions to guide and sensitize marketers to adopt good practices in handling this Amazonian delicacy.